Gender Equality and Inclusive Growth. (IMF Working Papers; Working Paper, 2021)
This paper considers various dimensions and sources of gender inequality and presents policies and best practices to address these. With women accounting for fifty percent of the global population, inclusive growth can only be achieved if it promotes gender equality. Despite recent progress, gender gaps remain across all stages of life, including before birth, and negatively impact health, education, and economic outcomes for women. The roadmap to gender equality has to rely on legal framework reforms, policies to promote equal access, and efforts to tackle entrenched social norms. These need to be set in the context of arising new trends such as digitalization, climate change, as well as shocks such as pandemics.